Helping and hurting others: Person and situation effects on aggressive and prosocial behavior as assessed by the Tangram task. Issue 2 (14th September 2016) - Saleem, Muniba; Barlett, Christopher P.; Anderson, Craig A.; Hawkins, Ian
Abstract : The Tangram Help/Hurt Task is a laboratory‐based measure designed to simultaneously assess helpful and hurtful behavior. Across five studies we provide evidence that further establishes the convergent and discriminant validity of the Tangram Help/Hurt Task. Cross‐sectional and meta‐analytic evidence finds consistently significant associations between helpful and hurtful scores on the Tangram Task and prosocial and aggressive personality traits. Experimental evidence reveals that situational primes known to induce aggressive and prosocial behavior significantly influence helpful and hurtful scores on the Tangram Help/Hurt Task. Additionally, motivation items in all studies indicate that tangram choices are indeed associated with intent of helping and hurting. We discuss the advantages and limitations of the Tangram Help/Hurt Task relative to established measures of helpful and hurtful behavior. Aggr. Behav. 43:133–146, 2017. © 2016 Wiley Periodicals, Inc.